Pyrosequencing 16S rRNA genes of bacteria associated with wild tiger mosquito Aedes albopictus: a pilot study - Minard, Guillaume; Tran, Florence-Hélène; Dubost, Audrey; Tran-Van, Van; Mavingui, Patrick; Valiente Moro, Claire (Frontiers in Cellular and Infection Microbiology, 2014)
The Asian tiger mosquito Aedes (Stegomya) albopictus is an invasive species that has spread across the world in the last two decades, showing a great capacity to adapt to contrasting climates and environments. While demonstrated in many insects, the contribution of bacterial symbionts in Aedes ecology is a challenging aspect that needs to be investigated however. Some bacterial species have already been identified in Ae. albopictus using classical methods, but a more accurate survey of mosquito-associated bacterial diversity is needed to decipher the potential biological functions of bacterial symbionts in mediating or constraining insect adaptation. We surveyed the bacteria associated with field populations of Ae. albopictus from Madagascar by pyrosequencing 16S rRNA gene amplicons. Different aspects of amplicon preparation and sequencing depth were tested to optimise the breadth of bacterial diversity identified. The results revealed that all mosquitoes collected from different sites have a bacterial microbiota dominated by a single taxon, Wolbachia pipientis, which accounted for about 99% of all 98,520 sequences obtained. Ae. albopictus is known to harbour two Wolbachia strains, wAlbA and wAlbB, and quantitative PCR was used to estimate the relative densities, i.e. the bacteria-to-host gene ratios, of the strains in individual mosquitoes. Relative densities were between 6.25 × 100.01 and 5.47 × 100.1 for wAlbA and between 2.03 × 100.1 and 1.4 × 101 for wAlbB. Apart from Wolbachia, a total of 32 bacterial taxa were identified at the genus level using the different in method variations. Diversity index values were low and probably underestimated the true diversity due to the high abundance of Wolbachia sequences vastly outnumbering sequences from other taxa. Further studies should implement alternative strategies to specifically discard from analysis any sequences from Wolbachia, the dominant endosymbiotic bacterium in Ae. albopictus from this area.